KAJIAN SISTEM DRAINASE PERUMAHAN VALLE VERDE DI DESA PASIRHALANG - Fuad Hasan (Universitas Widyatama, 2021)
Drainage is one of the basic facilities designed as a system to meet the needs of the community and is an important component in urban and residential planning. Valle Verde Residential located in the village of Pasirhalang, Cisarua District, Kabupaten Bandung Barat needs to make a study of the drainage system in order to avoid flooding or inundation. The purpose of this study is to determine the peak discharge and drainage system capacity of the plan. In this study the analysis carried out is the drainage zone, rainfall, average rainfall in the area, choosing the type of rainfall distribution, calculating the time concentration, determining the amount of rainfall intensity at the return period of 2 years, calculating flood discharge and calculating the capacity of the planned channel. From the results of the analysis and calculation it is known that for the main drainage channel can use an open channel with dimensions of height 0.25 m and a base width 0.30 m and freeboard 0.20 m. As for channels that are in residential areas, can use closed channels with diameter dimensions D = 0.30 m.